Educational Contribution of Umrah-E-Paigah in Asaf Jahi Period (International Journal of Food and Nutritional Sciences, 2022)
Mir Qamruddin Khan Nizam-ul-Mulk Asaf Jah-I established a new dynasty is calledSaltanath-E-Asafia in 1724 AD. The first capital was Aurangabad. After shifted to Hyderabadin the period of Nizam Ali Khan-II. The early period of Mir Qamruddin Khan was spent inbattles. Therefore, not many madrasas are mentioned during his period. "Paigah" wasestablished during the reign of Nizam Ali Khan-II